1114 Urbanicity And The Sleep-mental Health Relationship. (27th May 2020) - Moore, J; Seixas, A; Casimir, G; Nunes, J; Matadiaby, F; Khosrof, A; Jean-Louis, G
Abstract: Introduction: Inadequate sleep has been found to be associated with poor mental health. This is especially true in low-income and minority populations, who are concentrated in cities. It is not understood to what degree living in a city vs. a rural environment affects sleep and resulting mental health outcomes. This study seeks to understand how living in an urban environment affects the relationship between inadequate sleep and mental health. Methods: The study used data from the 2018 US Behavioral Risk Factor Surveillance System (BRFSS, ) a nationwide health dataset collected by telephone. Respondents were classified as living in either an urban or rural environment based on their zip code. Respondents reported hours of sleep per night and mental health status. This study classified mental health status based on whether the respondent reported one or more incidences of poor mental health in the previous 30 days. Results: After filtration, 348, 540 respondents were split into urban and rural groups. Binary logistic regression was run in each group to compare how much living in an urban environment contributed to the relationship between sleep duration and mental health. Sleep in the analysis was found to significantly contribute to both models; urban X 2 (15, N=295, 796) = 11, 485.70, p <0.001 rural X 2 (15, N=52, 744) = 2, 465.64, p <0.001. The estimated odds ratio resulted in a decrease of 13.9% [ Exp ( B ) = 0.861] in reported poor mental health for every unit increase of sleep in the urban population, and decrease of 14.9% [ Exp ( B ) = 0.851] in the rural population. Conclusion: In urban and rural dwellers, sleep duration predicted poor mental health. Contrary to expectations, sleep was more strongly tied to mental health in rural than urban populations. This was true even after controlling for sex, income, and education level. Further research should seek to understand how environment affects sleep and mental health. Support: This study was supported by funding from the NIH: R01MD007716, R01HL142066, R01AG056531, K01HL135452, and K07AG052685.